2017
DOI: 10.1016/j.ebiom.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

CRUSADE Score is Superior to Platelet Function Testing for Prediction of Bleeding in Patients Following Coronary Interventions

Abstract: Hypothetically, diminished platelet reactivity (PR) during dual antiplatelet therapy (DAPT) should cause extra major bleeding events (MBE), although definite evidence is lacking. Multiple scores have been proposed to stratify bleeding risk, but their predictive value during DAPT is unclear. We compared the performance of the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines (CRUSADE) with PR testing to predict MBE in Korean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(30 reference statements)
0
2
0
1
Order By: Relevance
“…6 7 We recently show that CRUSADE score was superior to platelet testing for predicting short-term, but not 1-year, bleeding in post–percutaneous coronary intervention (PCI) Korean patients treated with DAPT. 8…”
Section: Introductionmentioning
confidence: 99%
“…6 7 We recently show that CRUSADE score was superior to platelet testing for predicting short-term, but not 1-year, bleeding in post–percutaneous coronary intervention (PCI) Korean patients treated with DAPT. 8…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the CRUSADE score has been shown to be effective in predicting major bleeding in patients undergoing PCI, 13,14 and was shown to be even more valuable than the platelet reactivity test in PCI patients. 15 It can be used to predict mortality risk, similar to the GRACE risk score in ACS patients, 16 and to predict bleeding risk in STEMI patients. 17 The prognostic accuracy of the CRUSADE score can be used to predict major or moderate bleeding events even in non-invasively treated ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Шкала CRUSADE лучше предсказывает риск больших кровотечений в течение 1 мес. после ЧКВ у больных после ОКС, чем тестирование остаточной активности тромбоцитов методом VerifyNow -с-критерий для шкалы CRUSADE -0,81, а для тестирования агрегации тромбоцитов -0,61 [26]. CRUSADE является одной из самых точных шкал риска кровотечений -ее чувствительность составляет 80%, специфичность -73% [27].…”
Section: острый коронарный синдромunclassified